Social mobility and political regimes: Intergenerational mobility in Hungary, 1949-2017 - Pawel Bukowski; Gregory Clark; Attila Gáspár; Rita Pető (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
This paper measures social mobility rates in Hungary 1949-2017, for upper class and underclass families, using surnames to measure social status. In these years there were two very different social regimes. The first was the Hungarian People's Republic, 1949-1989, a Communist regime with an avowed aim of favouring the working class. Then the modern liberal democracy, 1989-2020, a free-market economy. We find five surprising things. First, social mobility rates were low for both upper- and lower-class families 1949-2017, with an underlying intergenerational status correlation of 0.6-0.8. Second, social mobility rates under communism were the same as in the subsequent capitalist regime. Third, the Romani minority throughout both periods showed even lower social mobility rates. Fourth, the descendants of the noble class in Hungary in the eighteenth century were still significantly privileged in 1949 and later. And fifth, while social mobility rates did not change measurably during the transition, the composition of the political elite changed fast and sharply.
Keywords: J62; N34; P36; 330; Social mobility; Status Inheritance; Institutions; Transition